Preparation method of nano Mg (OH) 2-PPS fabric composite diaphragm

By introducing free radicals onto the surface of a polyphenylene sulfide fabric membrane and growing Mg(OH)2 nanoparticles in situ, a nano-Mg(OH)2-PPS fabric composite membrane was prepared. This solved the problems of poor air tightness and weak ion transfer in alkaline water electrolysis hydrogen production systems, achieving membrane performance with low energy consumption and high safety.

CN121407150APending Publication Date: 2026-01-27ZHUZHOU TIMES NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511412654.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

In existing alkaline water electrolysis hydrogen production systems, polyphenylene sulfide membranes suffer from poor airtightness and weak ion transfer, resulting in high energy consumption and insufficient safety.

Method used

Free radicals are introduced onto the surface of a polyphenylene sulfide fabric membrane, and hydrophilic groups are introduced through a dilute acid solution reaction. Then, Mg(OH)2 nanoparticles are grown in situ in a magnesium salt solution, and a nano-Mg(OH)2-PPS fabric composite membrane is formed by hot pressing.

Benefits of technology

It improves the hydrophilicity and airtightness of the diaphragm, reduces the surface resistivity, enhances the stability and safety of the diaphragm, reduces the energy consumption of the electrolysis process, and avoids the risk of cross-leakage of hydrogen and oxygen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121407150A_ABST
    Figure CN121407150A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nano Mg (OH) 2-PPS fabric composite diaphragm, which comprises the following steps: introducing free radicals into a PPS fabric, carrying out acid treatment, and introducing an oxygen-containing hydrophilic functional group into a diaphragm interface to obtain a hydrophilic PPS fabric diaphragm. Then, Mg (OH) 2 grows on the fiber surface of the hydrophilic PPS fabric diaphragm by using an in-situ growth method, so that the composite membrane is endowed with high air tightness and low membrane resistance, and the alkali resistance and the electrolytic stability of the diaphragm are improved. The prepared composite membrane shows super-hydrophilicity, water drops can be completely absorbed within 1 second, and after 500 hours of tests are carried out in actual electrolysis production, various properties of the composite membrane are kept stable, and the composite membrane shows excellent long-term stability and electrolysis performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alkaline water electrolysis for hydrogen production technology, and particularly relates to a method for preparing a composite membrane. Background Technology

[0002] Hydrogen energy, hailed as the "ultimate energy of the 21st century," boasts advantages such as high production efficiency, low cost, and environmental friendliness. It plays a vital role in numerous sectors including transportation and industry, and is key to driving energy transformation. Among various hydrogen production technologies, alkaline water electrolysis is considered a crucial pathway for large-scale green hydrogen production due to its mature technology and low equipment costs, and it holds a dominant position in the hydrogen production industry.

[0003] In alkaline water electrolysis hydrogen production systems, the diaphragm, as the core component of the alkaline electrolyzer, directly determines the electrolysis efficiency, gas purity, system lifespan, and hydrogen production cost. Currently, commercial alkaline water electrolysis suffers from high energy consumption and safety issues during production, namely poor diaphragm airtightness and weak ion transport. Therefore, improving the diaphragm's airtightness and ion transport is particularly important. Traditional asbestos diaphragms have been banned due to their carcinogenicity, and currently, most commercially used hydrogen production diaphragms in China are polyphenylene sulfide (PPS) fabric diaphragms. Traditional PPS diaphragms are relatively inexpensive, but their hydrophobic properties result in relatively high energy consumption. Therefore, current research focuses on modifying PPS fabrics to improve the diaphragm's airtightness, enhance its ion transport efficiency, and reduce its hydrophobicity, thereby reducing energy consumption and improving safety. Summary of the Invention

[0004] To overcome the problems in the prior art, the present invention provides a method for preparing a nano-Mg(OH)2-PPS fabric composite membrane, which improves the hydrophilicity of the polyphenylene sulfide fabric membrane and enhances its airtightness, effectively solving the problems of high energy consumption and poor airtightness in the current alkaline water electrolysis hydrogen production process.

[0005] To solve the above-mentioned technical problems, the technical solution proposed by this invention is as follows: This invention provides a method for preparing a nano-Mg(OH)2-PPS fabric composite separator, comprising the following steps: S1. Free radicals are introduced onto the surface of the polyphenylene sulfide fabric membrane, and then the polyphenylene sulfide fabric membrane is immersed in a dilute strong acid solution. After the reaction, it is treated to obtain a dry hydrophilic modified polyphenylene sulfide fabric membrane.

[0006] S2. The hydrophilic modified polyphenylene sulfide fabric membrane obtained in step S1 is immersed in magnesium salt, and then the polyphenylene sulfide fabric membrane saturated with magnesium salt is immersed in dilute alkali solution. After the reaction, an alkali-resistant Mg(OH)2-containing composite polyphenylene sulfide fabric membrane is obtained.

[0007] S3. After drying the composite polyphenylene sulfide fabric diaphragm obtained in step S2, it is subjected to hot pressing to obtain a nano Mg(OH)2-PPS fabric composite diaphragm.

[0008] In this invention, free radicals are first introduced onto the surface of a polyphenylene sulfide (PPS) fabric membrane. Then, the PPS fabric membrane is immersed in a dilute strong acid solution to introduce oxygen-containing functional groups (hydroxyl, carbonyl, or sulfonic acid groups, etc.). By introducing hydrophilic groups, the hydrophilicity of the PPS fabric membrane is improved, and active sites are added to its surface. Next, Mg(OH)₂ is grown in situ on the PPS fabric fibers containing hydrophilic groups using a hydrothermal method. Magnesium salts are hydrothermally synthesized into magnesium hydroxide nanowires and nanoparticles in hot alkali, immobilizing the Mg(OH)₂ particles at the membrane pores or defects. Subsequently, the membrane undergoes hot pressing treatment, resulting in a denser surface and further improving the hydrophilicity and airtightness of the PPS membrane. The use of magnesium salts in this invention for in-situ growth of Mg(OH)₂ on the PPS fabric fibers is due to the superior toughness of magnesium hydroxide compared to other metals.

[0009] As an optional implementation, in the preparation method provided by the present invention, in step S1, free radicals are introduced on the surface of the polyphenylene sulfide fabric membrane using plasma irradiation technology.

[0010] In this invention, free radicals are generated by bombarding the material surface with plasma. These free radicals then generate hydrophilic groups such as carbonyl groups at the membrane interface in acid, thereby introducing free radicals onto the surface of the polyphenylene sulfide fabric membrane.

[0011] As an optional implementation method, in the preparation method provided by the present invention, in step S1, the reaction temperature of immersion in dilute acid solution is 0-100 °C, and the reaction time is 0.1-12 h.

[0012] The present invention involves immersing a polyphenylene sulfide fabric membrane in a dilute acid solution and then conducting a continuous reaction at 0-100℃ for 0.1-12 h, which can further improve the strength of the hydrophilic groups.

[0013] As an optional implementation method, in the preparation method provided by the present invention, in step S1, the drying temperature is 60-100 ℃ and the drying time is 2-3 h.

[0014] In this invention, the diaphragm is treated at 60-100℃ for 2 hours to completely remove residual moisture.

[0015] As an optional implementation, in the preparation method provided by the present invention, in step S1, the dilute strong acid solution is selected from one or more of nitric acid, sulfuric acid, acetic acid, formic acid or benzoic acid.

[0016] As an optional implementation, in the preparation method provided by the present invention, in step S2, the magnesium salt is selected from one or more of magnesium nitrate, magnesium chloride, phosphatase, or magnesium acetate.

[0017] As an optional implementation, in the preparation method provided by the present invention, in step S2, the dilute alkaline solution is selected from one or more of ammonia, urea, sodium hydroxide solution or potassium hydroxide.

[0018] As an optional implementation method, in the preparation method provided by the present invention, in step S2, the reaction temperature is 60-120 °C and the reaction time is 0.1-48 h.

[0019] In this invention, the reaction temperature is set at 60-120 ℃, which is beneficial for maintaining performance. Excessive temperature may damage the diaphragm.

[0020] As an optional implementation, in the preparation method provided by this invention, in step S3, the hot-pressing temperature is 100-180 ℃ and the pressure is 1-10 MPa. In this invention, the PPS membrane and Mg(OH)2 are thermally bonded under hot pressing. Controlling the hot-pressing temperature and pressure is beneficial to improving the dimensional stability of the membrane.

[0021] The polyphenylene sulfide fabric diaphragm in this invention is a commercially available product, typically with a thickness of 1000μm, 800μm, and 500μm, and the diaphragm weaving process is usually a twill weave process.

[0022] Based on the same technical concept, the present invention also provides the application of the nano-Mg(OH)2-PPS fabric composite membrane prepared by the above preparation method in alkaline water electrolysis for hydrogen production.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The nano-Mg(OH)2-PPS fabric composite membrane prepared by the three steps of modified polyphenylene sulfide fabric, in-situ growth of Mg(OH)2 nanoparticles and hot pressing treatment in this invention has good hydrophilicity and gas barrier properties, allowing only water molecules and hydroxide ions to pass through. The addition of hydrophilic Mg(OH)2 significantly reduces the surface resistance of the fabric membrane, effectively reducing the energy consumption in the electrolysis process. At the same time, the dense structure effectively avoids hydrogen and oxygen cross-linking, preventing safety problems caused by hydrogen and oxygen cross-linking during electrolysis.

[0024] (2) The nano-Mg(OH)2-PPS fabric composite membrane prepared by this invention solves the technical problem of hydrophilic nanoparticles easily falling off the surface of polyphenylene sulfide fabric, thus ensuring low energy consumption and high airtightness while having a better service life and enhancing its stability during use. It also has the characteristics of high porosity, high tensile strength and low surface resistance. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 Image of the yarn for a PPS fabric diaphragm; Figure 2 Image of a PPS fabric membrane after Mg(OH)2 growth; Figure 3 This is a photograph of a Mg(OH)2-PPS fabric composite membrane after hot pressing. Detailed Implementation

[0027] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to the accompanying drawings and preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0028] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0029] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0030] Example 1 Preparation of nano-Mg(OH)2-PPS fabric composite membrane (1) Preparation of hydrophilic PPS fabric membrane: First, PPS fabric was irradiated with plasma at room temperature for 10 minutes and then placed in 40% dilute sulfuric acid at 60℃ for 0.5 h of continuous reaction to introduce hydrophilic groups such as hydroxyl and sulfonic acid; after the reaction was completed, the membrane was removed and washed with distilled water several times to remove residual acid; finally, the membrane was treated at 100℃ for 1 h to completely remove residual moisture and obtain dry hydrophilic modified PPS fabric.

[0031] (2) In-situ growth of Mg(OH)2: First, a magnesium chloride solution with a concentration of 50 g / L was prepared, and 1 square meter of modified membrane was immersed in the magnesium chloride solution to saturate the membrane with magnesium chloride adsorption. The PPS membrane with adsorbed magnesium chloride was then immersed in a 50 g / L urea solution and reacted at 80 ℃ for 24 h. After the reaction system cooled to room temperature, the modified membrane was removed and washed to remove residual metal ions and Mg(OH)2 adhering to the surface. The yarn pattern of the PPS fabric membrane was examined by electron microscopy as shown in the figure. Figure 1 The image shown is of Mg(OH)2 after growth. Figure 2 As shown, this indicates that Mg(OH)2 is grown in situ on the surface of the PPS fabric diaphragm.

[0032] (3) After drying the obtained composite diaphragm, it was hot-pressed at 2 MPa and 140 °C for 1 min to obtain the final product. A picture of the actual product is shown below. Figure 3 As shown, it exhibits excellent hydrophilic properties.

[0033] Example 2 Preparation of nano-Mg(OH)2-PPS fabric composite membrane (1) Preparation of hydrophilic PPS fabric membrane: First, PPS fabric was irradiated with plasma at room temperature for 10 minutes and then placed in 10% nitric acid at room temperature for 0.5 h of continuous reaction to introduce hydrophilic groups such as hydroxyl, nitro, and amino groups. After the reaction was completed, the membrane was removed and washed with distilled water several times to remove residual acid. Finally, the membrane was treated at 100 °C for 2 h to completely remove residual moisture and obtain dry hydrophilic modified PPS fabric.

[0034] (2) In-situ growth of Mg(OH)2: First, prepare a magnesium nitrate solution with a concentration of 60 g / L, and immerse 1 square meter of modified membrane in the magnesium nitrate solution to saturate the membrane with magnesium nitrate adsorption. Immerse the PPS membrane with adsorbed magnesium nitrate in a 50 g / L urea solution and react at 90 ℃ for 24 h. After the reaction system cools to room temperature, remove the modified membrane and wash it to remove residual metal ions and oxides attached to the surface.

[0035] (3) After drying the obtained composite membrane, hot-press it at 180 °C for 1 min under a pressure of 5 MPa to obtain the final product.

[0036] Example 3 Preparation of nano-Mg(OH)2-PPS fabric composite membrane (1) Preparation of hydrophilic PPS fabric membrane: First, PPS fabric was irradiated with plasma at room temperature for 30 minutes and then placed in 20% acetic acid at 60℃ for 2 h of continuous reaction to introduce hydrophilic groups such as hydroxyl and carboxyl groups; after the reaction was completed, the membrane was removed and washed with distilled water several times to remove residual acid; finally, the membrane was treated at 100℃ for 1 h to completely remove residual moisture and obtain dry hydrophilic modified PPS fabric.

[0037] (2) In-situ growth of Mg(OH)2: First, prepare a magnesium acetate solution with a concentration of 50 g / L, and immerse 1 square meter of modified membrane in the magnesium acetate solution to saturate the membrane with magnesium acetate adsorption. Immerse the PPS membrane with adsorbed magnesium acetate in a 50 g / L ammonia solution and react at 90 °C for 24 h. After the reaction system cools to room temperature, remove the modified membrane and wash it to remove residual metal ions and Mg(OH)2 coated on the surface.

[0038] (3) After drying the obtained composite membrane, hot pressing is performed at 100 ℃ for 5 min under a pressure of 10 MPa to obtain the final product.

[0039] Example 4 Preparation of nano-Mg(OH)2-PPS fabric composite membrane (1) Preparation of hydrophilic PPS fabric membrane: First, PPS fabric was irradiated with plasma at room temperature for 60 minutes and then placed in 30% formic acid at 60℃ for 2 hours to introduce hydrophilic groups such as hydroxyl and carboxyl groups. After the reaction was completed, the membrane was removed and washed with distilled water several times to remove residual acid. Finally, the membrane was treated at 100℃ for 1 hour to completely remove residual moisture and obtain dry hydrophilic modified PPS fabric.

[0040] (2) In-situ growth of Mg(OH)2: First, prepare a magnesium acetate solution with a concentration of 50 g / L, and immerse 1 square meter of modified membrane in the magnesium acetate solution to saturate the membrane with magnesium acetate adsorption. Immerse the PPS membrane with adsorbed magnesium acetate in a 50 g / L ammonia solution and react at 90 °C for 24 h. After the reaction system cools to room temperature, remove the modified membrane and wash it to remove residual metal ions and Mg(OH)2 coated on the surface.

[0041] (3) After drying the obtained composite membrane, hot-press it at 180 °C for 2 min under a pressure of 2 MPa to obtain the final product.

[0042] Example 5 Preparation of nano-Mg(OH)2-PPS fabric composite membrane (1) Preparation of hydrophilic PPS fabric membrane: First, PPS fabric was irradiated with plasma at room temperature for 60 minutes and then placed in 30% benzoic acid at 60℃ for 1 h of continuous reaction to introduce hydrophilic groups such as hydroxyl, carboxyl, and carbonyl groups. After the reaction was completed, the membrane was removed and washed with distilled water several times to remove residual acid. Finally, the membrane was treated at 100℃ for 1 h to completely remove residual moisture and obtain dry hydrophilic modified PPS fabric.

[0043] (2) In-situ growth of Mg(OH)2: First, prepare a magnesium acetate solution with a concentration of 50 g / L, and immerse 1 square meter of modified membrane in the magnesium acetate solution to saturate the membrane with magnesium acetate adsorption. Immerse the PPS membrane with adsorbed magnesium acetate in a 50 g / L urea solution and react at 100 °C for 24 h. After the reaction system cools to room temperature, remove the modified membrane and wash it to remove residual metal ions and Mg(OH)2 adhering to the surface.

[0044] (3) After drying the obtained composite membrane, hot-press it at 180 °C for 5 min under a pressure of 1 MPa to obtain the final product.

[0045] Example 6 Preparation of nano-Mg(OH)2-PPS fabric composite membrane (1) Preparation of hydrophilic PPS fabric membrane: First, PPS fabric was irradiated with plasma at room temperature for 60 minutes and then placed in 5% sulfuric acid at 100 °C for 1 h of continuous reaction to introduce hydrophilic groups such as hydroxyl and sulfuric acid. After the reaction was completed, the membrane was removed and washed with distilled water several times to remove residual acid. Finally, the membrane was treated at 100 °C for 1 h to completely remove residual moisture and obtain dry hydrophilic modified PPS fabric.

[0046] (2) In-situ growth of Mg(OH)2: First, prepare a magnesium sulfate solution with a concentration of 50 g / L, and immerse 1 square meter of modified membrane in the magnesium sulfate solution to saturate the membrane with magnesium sulfate adsorption. Immerse the PPS membrane with magnesium sulfate adsorption in a 50 g / L urea solution and react at 100 °C for 48 h. After the reaction system cools to room temperature, remove the modified membrane and wash it to remove residual metal ions and Mg(OH)2 coated on the surface.

[0047] (3) After drying the obtained composite membrane, hot pressing is performed at 100 °C for 10 min under a pressure of 8 MPa to obtain the final product.

[0048] Comparative Example 1 Take a pure polyphenylene sulfide fabric membrane of the same size, soak the membrane in deionized water for more than 24 hours, take it out and wash it 4 times with anhydrous ethanol and deionized water respectively, and dry the membrane at 60 ℃ for 6 hours to remove impurities in the polyphenylene sulfide fabric membrane, and obtain a pure polyphenylene sulfide fabric membrane with an actual thickness of 502 μm.

[0049] Comparative Example 2 Cut a standard thickness polyphenylene sulfide fabric diaphragm to a suitable size. Measure 20 L of 60% concentrated sulfuric acid solution and place it in a container. Immerse the PPS fabric diaphragm in the sulfuric acid solution and place it in a constant temperature oven at 80 ℃ for a continuous reaction for 2-3 h to graft sulfonic acid groups. After the reaction is complete, remove the diaphragm and wash it several times with distilled water to remove residual sulfuric acid. Finally, treat the diaphragm at 100 ℃ for 2 h to completely remove residual moisture, obtaining a dry sulfonic acid modified PPS fabric.

[0050] Comparative Example 3 The difference from Example 1 is that a 50 g / L zirconium oxychloride solution is prepared instead of a 50 g / L magnesium chloride solution.

[0051] Comparative Example 4 The difference from Example 1 is that the hot pressing reaction in step (3) was not carried out.

[0052] Comparative Example 5 The difference from Example 1 is that the dilute sulfuric acid in step (1) is replaced with saturated carbonic acid.

[0053] Comparative Example 6 Preparation of nano-Mg(OH)2-PPS fabric composite membrane The difference from Example 1 is that the dilute sulfuric acid in step (1) is replaced with 20% phosphoric acid.

[0054] Performance testing The porosity of the alkaline water electrolysis hydrogen production composite membrane prepared above was measured using the wet-dry gravimetric method. The hydrophilicity of the membrane was assessed by measuring its surface water contact angle. The tensile properties of the membrane were measured according to the Chinese national standard GB-T16491-1996 for the electronics industry. The bubble point pressure was used to measure the membrane's airtightness; bubble point pressure is a key indicator of membrane airtightness, representing the minimum pressure required for gas to penetrate the membrane. A self-built electrochemical impedance spectroscopy (EIS) testing system was used for surface resistance testing. Surface resistance refers to the resistance value per unit area of ​​the membrane, which directly affects the energy consumption of the electrolyzer. Specifically, the membrane was completely immersed in anhydrous ethanol for 3 hours, thoroughly wetted, and then completely immersed in a 30% potassium hydroxide solution for 24 hours. The membrane was then sandwiched within a small square window in the middle of a custom-made polytetrafluoroethylene (PTFE) plate, and surface resistance was measured using a nickel foam electrode.

[0055] The test results are shown in Table 1 below.

[0056] Table 1: Diaphragm performance test results in the examples and comparative examples

[0057] As shown in Table 1, compared with the unmodified pure polyphenylene sulfide fabric-type alkaline water electrolysis hydrogen production diaphragm used in Comparative Example 1, the excellent hydrophilicity of Mg(OH)2 improves the hydrophobicity of the diaphragm, making it more hydrophilic and achieving a lower sheet resistance. Subsequent hot-pressing treatment significantly improves the airtightness of the resulting diaphragm. The growth of Mg(OH)2 greatly increases the mechanical strength of the diaphragm. Hot pressing improves both the airtightness and mechanical strength, but also increases the membrane resistance. Compared with other hydroxides, Mg(OH)2 exhibits better alkali resistance, hydrophilicity, and flexibility, effectively reducing the shedding of inorganic substances from the composite diaphragm.

[0058] In Comparative Example 2, the sulfonated hydrophilic polyphenylene sulfide fabric diaphragm was prepared. The diaphragm had strong hydrophobic properties, but after hot pressing, the airtightness of the diaphragm was also poor.

[0059] In Comparative Example 3, Zr(OH)4 was used to replace Mg(OH)2. The cost of Zr(OH)4 is significantly higher than that of Mg(OH)2, resulting in a high price for the composite membrane. Furthermore, although the hydrophilicity and airtightness of the membrane met the requirements after replacing Mg(OH)2 with Zr(OH)4, Mg(OH)2 has good toughness, while Zr(OH)4 is brittle. The membrane in Comparative Example 3 was prone to powdering during use, and the composite Zr(OH)4 easily detached from the fabric membrane, affecting the membrane's performance.

[0060] Comparative Example 4: The Mg(OH)4-PPS fabric composite diaphragm was not hot-pressed, resulting in better hydrophilicity, but its mechanical properties and airtightness deviated.

[0061] Compared to the strong acids in the examples, the composite membranes prepared using carbonic acid and phosphoric acid in Comparative Examples 5 and 6 have relatively poor hydrophilicity or airtightness.

[0062] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. However, it should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a nano-Mg(OH)2-PPS fabric composite membrane, characterized in that, Includes the following steps: S1. Free radicals are introduced on the surface of the polyphenylene sulfide fabric membrane, and then the polyphenylene sulfide fabric membrane is immersed in a dilute strong acid solution. After the reaction, it is treated to obtain a dry hydrophilic modified polyphenylene sulfide fabric membrane. S2. The hydrophilic modified polyphenylene sulfide fabric membrane obtained in step S1 is soaked in magnesium salt, and then the polyphenylene sulfide fabric membrane saturated with magnesium salt is immersed in a dilute alkaline solution. After the reaction, an alkali-resistant Mg(OH)2-containing composite polyphenylene sulfide fabric membrane is obtained. S3. After drying the composite polyphenylene sulfide fabric diaphragm obtained in step S2, it is subjected to hot pressing to obtain a nano Mg(OH)2-PPS fabric composite diaphragm.

2. The method for preparing the nano-Mg(OH)2-PPS fabric composite membrane according to claim 1, characterized in that, In step S1, free radicals are introduced onto the surface of the polyphenylene sulfide fabric membrane using plasma irradiation technology.

3. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S1, the reaction temperature of immersion in dilute acid solution is 0-100 ℃, and the reaction time is 0.1-12 h.

4. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S1, the drying temperature is 60-100 ℃ and the drying time is 2-3 h.

5. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S1, the dilute strong acid solution is selected from one or more of nitric acid, sulfuric acid, acetic acid, formic acid, or benzoic acid.

6. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S2, the magnesium salt is selected from one or more of magnesium nitrate, magnesium chloride, phosphatase, or magnesium acetate.

7. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S2, the dilute alkaline solution is selected from one or more of ammonia, urea, sodium hydroxide solution, or potassium hydroxide.

8. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S2, the reaction temperature is 60-120 ℃ and the reaction time is 0.1-48 h.

9. The method for preparing the nano-Mg(OH)₂-PPS fabric composite membrane according to claim 1, characterized in that, In step S3, the hot pressing temperature is 100-180 ℃ and the pressure is 1-10 MPa.

10. The application of the nano-Mg(OH)2-PPS fabric composite membrane prepared by the preparation method according to any one of claims 1-9 in alkaline water electrolysis for hydrogen production.